Query Expansion for Quran French Text Retrieval Using Semantic Search - Yusuf, Nuhu; Mohd Yunus, Mohd Amin; Wahid, Norfaradilla (Journal of Soft Computing and Data Mining, 2020)
Quran translation search are now gaining interest of many researchers in the field of Quran informatics. Current Quran translation search performance still needs to be improving. Despite the fact that many researchers contribute on its performance, few considered translation performance on semantic search for query expansion in French text retrieval. In this study, the performance of Quran translation search is proposed using semantic search. The experiment was carried out using 6236 verses of the holy Quran translated by Hamidullah. The results shows that the proposed query expansion based on semantic search perform best and achieved almost 36% improvement. Experiment on the Quran ontology document should serve as the further research direction